(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Adolescents are weakly aware of reproductive health issues. Regarding the high importance of reproductive health and self-esteem level, this study aims at determining the relationship between the awareness of reproductive health and self-esteem. Methods: The population of this cross-sectional study, was the first-semester students who entered into Shahroud University of medical sciences in January 2017. The demographic information, Cooper Smith scale for self-esteem and reproductive health researcher-made scale, were completed by the students. SPSS v16 software and T-test and Chi-square statistical tests were used in analyzing the data. Results: 105 students participated in the study. The average age of students was 20.2 ±1.8. The average score of reproductive health scale was 51.48±16.24, and the average score for self-esteem questions was 32.91±13.0. There was no statistical difference between male and female groups. There was a significant relationship between the awareness of reproductive health and self-esteem level (r=0.25 and P=0.001). conclusions: In the current research, there was a significant relationship between the awareness of reproductive health and self-esteem level. It is suggested that the youth receive more education on reproductive health because this can lead to mental health, in addition to physical health.